13 DE MAIO DE 1888 UMA RELEITURA DOS EVENTOS ABOLICIONISTAS DO SÉCULO XIX PELA CRÔNICA DE LIMA BARRETO (Muitas Vozes, 2022)
This article discusses the ways in which the chronicle by Afonso Henriques de Lima Barreto (1881-1922) dialogued with the official discourses of progress, among which the abolitionist novelty was inserted. From the analysis of the treatment that the literate performs the historical events around the celebrations of the “Áurea Act”, our analysis identifies an elaborate expedient organized by the chronicler to communicate other temporalities. In the writer's commitment to the marginalized by official speeches, the record achieved could be read as an authentic literary intervention in the narratives that deal with abolitionist events in the country.